Meta-aramid fibrid and preparation method thereof

Through the prepolymerization and polymerization of m-phenylenediamine and isophthalyl chloride, combined with high shear forming process, the problem of unstable quality of meta-aramidite fibers was solved, and a high mechanical properties and high temperature resistance were prepared. Fiber, suitable for the production of high-performance aramid paper.

CN119121437APending Publication Date: 2024-12-13CHAMBROAD CHEM IND RES INST CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411342361.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The quality of the meta-aramid aramid fibers sold on the market is uneven, especially the chopped aramid fibers, which cause low strength after paper, especially low tear strength.

Method used

By prepolymerizing m-phenylenediamine and isophthalyl chloride in a reactor, and then polymerizing in a twin-screw reactor, diluting and neutralizing, the meta-aramid fiber stock solution was obtained and cut at high shear Under the action of the solidification bath, the meta-aramid fiber was obtained by washing.

Benefits of technology

The prepared meta-aramid aramid precipitated fiber has high tensile strength and tear strength, and is suitable for the preparation of high-performance aramid paper products. It has a simple process and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of meta-aramid fibrid, which comprises the following steps: a) pre-polymerizing m-phenylenediamine and isophthaloyl dichloride in a reaction kettle to obtain a prepolymer; b) polymerizing, diluting and neutralizing the prepolymer in a twin-screw reactor to obtain a meta-aramid fibrid stock solution; and c) dispersing and forming the meta-aramid fibrid stock solution and a coagulating bath under the action of high shear, and washing the obtained product with water to obtain the meta-aramid fibrid. The invention also provides the meta-aramid fibrid prepared by the method provided by the technical scheme. The meta-aramid fibrid prepared by the method provided by the invention is in a film shape or a fiber strip shape, and has excellent mechanical properties, chemical stability and flame retardance and outstanding high temperature resistance and insulating property. The preparation method of the meta-aramid fibrid, provided by the invention, is simple in process, stable in product performance and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical synthesis, and in particular to a meta-aramid fibrid and a preparation method thereof. Background Art

[0002] The scientific name of meta-aramid is poly(m-phenylene isophthalamide), commonly known as aramid 1313. As a key raw material for high-performance paper-based materials, it plays a role in filling chopped fibers and bonding in meta-aramid paper. Its structure and performance are crucial to paper sheet formation and paper quality.

[0003] Meta-aramid fibrids are particles obtained by injecting meta-aramid resin solution into the precipitation liquid in the form of a thin stream under high shearing action. They are generally in the form of films or strips and have excellent mechanical properties, chemical stability, flame retardancy, outstanding high temperature resistance and insulation properties. However, the quality of commercially available meta-aramid fibrids varies, and the strength of paper made from aramid short fibers, especially the tear strength, is lower. Summary of the invention

[0004] In view of this, the purpose of the present application is to provide a meta-aramid fibrid and a preparation method thereof. The meta-aramid fibrid provided in the present application has high tensile strength and tear strength, and the preparation method is simple.

[0005] The present application provides a method for preparing meta-aramid fibrid, comprising the following steps:

[0006] a) prepolymerizing m-phenylenediamine and isophthaloyl chloride in a reaction kettle to obtain a prepolymer;

[0007] b) polymerizing the prepolymer in a twin-screw reactor, and obtaining a meta-aramid fibrillation stock solution after dilution and neutralization;

[0008] c) dispersing and molding the meta-aramid fibrid stock solution and the coagulation bath under the action of high shear, and washing the obtained product with water to obtain the meta-aramid fibrid.

[0009] In some specific implementations, the step a) includes:

[0010] The first part of isophthaloyl chloride is mixed with the m-phenylenediamine solution to perform a first prepolymerization;

[0011] The second portion of isophthaloyl chloride is mixed with the first prepolymer to carry out a second prepolymerization to obtain a prepolymer.

[0012] In some specific implementations, the isophthaloyl chloride in the first part accounts for 10% to 90% of the total amount of isophthaloyl chloride in the first part and the second part.

[0013] In some specific implementations, the molar ratio of the total amount of isophthaloyl chloride in the first part and the second part to the m-phenylenediamine is 1.0-1.01:1;

[0014] The temperature of the first prepolymerization and the second prepolymerization is independently -5°C to 5°C;

[0015] The time of the first prepolymerization is 10 min to 30 min, and the time of the second prepolymerization is 20 min to 40 min.

[0016] In some specific implementations, the solvent for prepolymerization in step a) is N-methylpyrrolidone;

[0017] The stirring speed of the prepolymerization is 500 rpm to 1500 rpm.

[0018] In some specific implementations, the rotation speed of the twin-screw reactor is 500 rpm to 1000 rpm; and the polymerization temperature is 40° C. to 60° C.

[0019] In some specific implementations, the meta-aramid fibrillation stock solution has a solid content of 6% to 11% and an inherent viscosity of 1.0 dL / g to 2.1 dL / g.

[0020] In some specific implementations, in step c), the coagulation bath is a mixture of N-methylpyrrolidone and water;

[0021] The volume content of N-methylpyrrolidone in the coagulation bath is 5% to 30%;

[0022] The temperature of the coagulation bath is 0°C to 40°C.

[0023] In some specific implementations, the high shear rotation speed is 3000 rpm~8000 rpm.

[0024] The present application also provides a meta-aramid fiber prepared by the method described in the above technical solution.

[0025] The present application first prepolymerizes meta-phenylenediamine and isophthaloyl chloride in a reactor to obtain a prepolymer, and then transfers the prepolymer to a twin-screw reactor for polymerization, and obtains a meta-aramid fibrillation stock solution after dilution and neutralization; finally, the meta-aramid fibrillation stock solution and a coagulation bath are dispersed and formed under the action of high shear, and the obtained product is washed with water to obtain meta-aramid fibrillation. The meta-aramid fibrillation prepared by the method provided in the present application has a film-like or fiber-like morphology, and has excellent mechanical properties, chemical stability, flame retardancy, and outstanding high temperature resistance and insulation properties, and is particularly suitable for preparing aramid paper products. The preparation method of meta-aramid fibrillation provided by the present invention has a simple process, stable product performance, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic flow chart of a method for preparing meta-aramid fibrid provided in an embodiment of the present application;

[0027] Figure 2 This is a SEM image of the meta-aramid fiber prepared in the embodiment of the present application at a small magnification;

[0028] Figure 3 This is a SEM image of the meta-aramid fiber prepared in the example of the present application at a high magnification. DETAILED DESCRIPTION

[0029] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0030] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0031] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0032] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.

[0033] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0034] The present application provides a method for preparing meta-aramid fibrid, comprising the following steps:

[0035] a) prepolymerizing m-phenylenediamine and isophthaloyl chloride in a reaction kettle to obtain a prepolymer;

[0036] b) polymerizing the prepolymer in a twin-screw reactor, and obtaining a meta-aramid fibrillation stock solution after dilution and neutralization;

[0037] c) dispersing and molding the meta-aramid fibrid stock solution and the coagulation bath under the action of high shear, and washing the obtained product with water to obtain the meta-aramid fibrid.

[0038] The present application first prepolymerizes meta-phenylenediamine and isophthaloyl chloride in a reactor to obtain a prepolymer, and then transfers the prepolymer to a twin-screw reactor for polymerization, and obtains a meta-aramid fibrillation stock solution after dilution and neutralization; finally, the meta-aramid fibrillation stock solution and a coagulation bath are dispersed and formed under the action of high shear, and the obtained product is washed with water to obtain meta-aramid fibrillation. The meta-aramid fibrillation prepared by the method provided in the present application has a film-like or fiber-like morphology, and has excellent mechanical properties, chemical stability, flame retardancy, and outstanding high temperature resistance and insulation properties, and is particularly suitable for preparing aramid paper products. The preparation method of meta-aramid fibrillation provided by the present invention has a simple process, stable product performance, and is suitable for industrial production.

[0039] The present application uses m-phenylenediamine and isophthaloyl chloride as raw materials to prepare aramid fiber. First, m-phenylenediamine and isophthaloyl chloride are prepolymerized in a reactor to obtain a prepolymer. Specifically, the present application first adds a solvent to a reactor, then adds m-phenylenediamine, and after dissolving, adds isophthaloyl chloride for prepolymerization. In some specific implementations, the solvent includes but is not limited to N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, etc., preferably N-methylpyrrolidone. In some specific implementations, m-phenylenediamine is dissolved at low temperature, and the low temperature is preferably -5°C~5°C, preferably -3°C~3°C. Specifically, the solvent can be first reduced to a low temperature, and then m-phenylenediamine is added for dissolution. In some specific implementations, the concentration of the m-phenylenediamine is 1.0mol / L~1.4mol / L, preferably 1.0mol / L~1.2mol / L. In some specific implementations, m-phenylenediamine is preferably dissolved under stirring, and the stirring speed is 500 rpm to 1500 rpm, preferably 800 rpm to 1300 rpm.

[0040] In some specific implementations, the present application preferably adds isophthaloyl chloride in two steps, specifically:

[0041] The first part of isophthaloyl chloride is mixed with the m-phenylenediamine solution to perform a first prepolymerization;

[0042] The second portion of isophthaloyl chloride is mixed with the first prepolymer to carry out a second prepolymerization to obtain a prepolymer.

[0043] Specifically, after dissolving the m-phenylenediamine, add the first part of isophthaloyl chloride thereto, perform the first prepolymerization, and then add the second part of isophthaloyl chloride to perform the second prepolymerization to obtain a prepolymer. In some specific implementations, the isophthaloyl chloride of the first part accounts for 10% to 90% of the total amount of isophthaloyl chloride of the first part and the second part, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%. In some specific implementations, the molar ratio of the total amount of isophthaloyl chloride of the first part and the second part to the m-phenylenediamine is 1.0 to 1.01:1, for example, 1.001:1, 0.003:1, 1.005:1, 0.006:1, 1.008:1, 1.01:1, etc. In some specific implementations, the temperature of the first prepolymerization and the second prepolymerization is independently -5°C to 5°C, preferably -3°C to 3°C. In some specific implementations, the time of the first prepolymerization is 10min to 30min, for example, 1min, 15min, 20min, 25min and 30min. In some specific implementations, the time of the second prepolymerization is 20min to 40min, for example, 20min, 25min, 30min, 35min and 40min. In some specific implementations, the first prepolymerization and the second prepolymerization are carried out under stirring, and the stirring speed is 500rpm to 1500rpm, preferably 800rpm to 1300rpm.

[0044] After the prepolymer is obtained, it is transferred to a twin-screw reactor for polymerization. The present application has no special restrictions on the twin-screw reactor, and a twin-screw polymerization reactor familiar to those skilled in the art can be used. In some specific implementations, the rotation speed of the twin-screw reactor is 500rpm~1000rpm, preferably 800rpm~1300rpm; in some specific implementations, the polymerization temperature is 40℃~60℃, preferably 45℃~55℃. It can be understood by those skilled in the art that the polymerization temperature is the temperature of the twin-screw reactor.

[0045] After the polymerization is completed, the meta-aramid polymerization product is diluted and neutralized to obtain a meta-aramid fibrillation stock solution. The present application has no restrictions on the specific parameters of the dilution and neutralization, which can be selected according to the needs. In some specific implementations, the dilution is diluted with an organic solvent. In some specific implementations, an alkaline reagent is used for neutralization, and the alkaline reagent includes but is not limited to at least one of sodium hydroxide, calcium hydroxide, and pyridine. When it is a mixture of multiple substances, the present application has no special restrictions on the amount of each specific substance.

[0046] In some specific implementations, after dilution and neutralization, the solid content of the obtained meta-aramid fiber precipitate solution is 6%~11%, preferably 8%~10%; its logarithmic viscosity is 1.0dL / g~2.1dL / g, preferably 1.2dL / g~1.8 dL / g.

[0047] After obtaining the meta-aramid fibrid stock solution, it is dispersed and formed in a coagulation bath under the action of high shear, and the meta-aramid fibrid is obtained after washing. In some specific implementations, the coagulation bath is a mixture of N-methylpyrrolidone and water; the volume content of the N-methylpyrrolidone is 5% to 30%, preferably 10% to 25%, and more preferably 15% to 20%. Specifically, the present application injects the meta-aramid fibrid stock solution and the coagulation bath into a high shear dispersion molding device at the same time, and coagulates in the coagulation bath under the action of high shear force to form a sheet or film product. In some specific implementations, the temperature of the coagulation bath is 0°C to 40°C, preferably 5°C to 35°C, more preferably 10°C to 30°C, and most preferably 15°C to 25°C. In some specific implementations, the high shear dispersion molding device can be a precipitator or an emulsifier. In some specific implementations, the high shear rotation speed is 3000 rpm to 8000 rpm, preferably 3500 rpm to 7500 rpm, and more preferably 4000 rpm to 7000 rpm.

[0048] After dispersion and forming, the present application preferably performs multiple water washing on the obtained product. The present application has no special requirements on the parameters of the water washing, and the washing can be performed according to the parameters commonly used by those skilled in the art. After multiple water washing, strip-shaped or film-shaped meta-aramid fiber precipitates are obtained.

[0049] See also Figure 1 , Figure 1 A schematic flow chart of a method for preparing meta-aramid fibrid provided in an embodiment of the present application, wherein meta-phenylenediamine and isophthaloyl chloride are first prepolymerized in a reactor to obtain a prepolymer; the prepolymer is then polymerized in a twin-screw reactor, and after dilution and neutralization, a meta-aramid fibrid stock solution is obtained; the meta-aramid fibrid stock solution and a coagulation bath are dispersed and formed under the action of high shear, and then after multiple water washings, the meta-aramid fibrid is obtained.

[0050] The mechanical beating degree of the meta-aramid fibrid provided in the present application is 30SR-50SR, for example, 30 SR, 35 SR, 40 SR, 45 SR, 50 SR, etc.

[0051] The present application also provides a method for preparing aramid insulation paper, comprising the following steps:

[0052] a) prepolymerizing m-phenylenediamine and isophthaloyl chloride in a reaction kettle to obtain a prepolymer;

[0053] b) polymerizing the prepolymer in a twin-screw reactor, and obtaining a meta-aramid fibrillation stock solution after dilution and neutralization;

[0054] c) dispersing and forming the meta-aramid fibrid stock solution and the coagulation bath under the action of high shear, and washing the obtained product with water to obtain the meta-aramid fibrid;

[0055] d) mixing the meta-aramid fibrid with aramid chopped fibers to make paper, and subjecting the mixture to high temperature and high pressure treatment to obtain aramid insulating paper.

[0056] After preparing the meta-aramid fibrid according to the method described above, it is mixed with aramid short fibers and then papermaking is performed, and aramid insulating paper is obtained after high temperature and high pressure treatment. The present application has no special restrictions on the mass ratio of the meta-aramid fibrid to the aramid short fibers, for example, it can be 1:1. The present application has no special restrictions on the papermaking, which can be carried out in a papermaking machine. The present application has no special restrictions on the high temperature and high pressure treatment, and those skilled in the art can select according to needs.

[0057] The aramid insulation paper prepared in the present application has good mechanical properties, for example, its tensile strength can reach more than 3500N / m, and its tear strength can reach 2000mN.

[0058] The present application first prepolymerizes meta-phenylenediamine and isophthaloyl chloride in a reactor to obtain a prepolymer, and then transfers the prepolymer to a twin-screw reactor for polymerization, and obtains a meta-aramid fibrillation stock solution after dilution and neutralization; finally, the meta-aramid fibrillation stock solution and a coagulation bath are dispersed and formed under the action of high shear, and the obtained product is washed with water to obtain meta-aramid fibrillation. The meta-aramid fibrillation prepared by the method provided in the present application has a film-like or fiber-like morphology, and has excellent mechanical properties, chemical stability, flame retardancy, and outstanding high temperature resistance and insulation properties, and is particularly suitable for preparing aramid paper products. The preparation method of meta-aramid fibrillation provided by the present invention has a simple process, stable product performance, and is suitable for industrial production.

[0059] The meta-aramid fibrid and the preparation method thereof provided in the present application are further described below in conjunction with the embodiments.

[0060] Example 1

[0061] Add N-methylpyrrolidone into the reactor and cool it to 5°C. Add m-phenylenediamine to dissolve it into a 1.0 mol / L solution. The polymerization speed is 500 rpm. Add isophthaloyl chloride twice with an interval of 10 minutes. The molar ratio of isophthaloyl chloride to m-phenylenediamine is 1.01:1. The first isophthaloyl chloride feed accounts for 10%. After the prepolymerization is completed, the polymer product enters the twin screw for polymerization. The twin screw speed is 500 rpm and the temperature is controlled at 40°C. After the polymerization reaction is completed, it is diluted and neutralized. The solid content of the diluted meta-aramid stock solution is 7%, and the logarithmic viscosity is 1.0 dL / g. Configure a coagulation bath, N-methylpyrrolidone accounts for 10%, and the rest is water. Keep the coagulation bath temperature at 40°C. Inject the meta-aramid stock solution and the coagulation bath into the high shear dispersion molding equipment at the same time, with a speed of 4000 rpm. The collected product was subjected to multiple water washing steps to obtain a meta-aramid fiber precipitation product, the mechanical beating degree of which was 30SR and the fiber length was 0.5 mm. The results were observed under a microscope. Figure 2 and Figure 3 , Figure 2 This is a SEM image of the meta-aramid fiber prepared in the embodiment of the present application at a small magnification. Figure 2 This is a SEM image of the meta-aramid fiber prepared in the embodiment of the present application at a high magnification. Figure 2 and Figure 3 It can be seen that the fiber morphology of the meta-aramid fibrid prepared in the present application is in the form of strips or films.

[0062] The above-mentioned meta-aramid fiber precipitation and aramid short-cut fibers are made into paper sheets in a papermaking machine at a ratio of 1:1. After high temperature and high pressure treatment, the paper sheets have a thickness of 0.05 mm, a tensile strength of 3500 N / m, a tear strength of 2000 mN, and an air permeability of 0.05 μm / (Pa·s).

[0063] Comparative Example 1

[0064] The difference from Example 1 is that after the prepolymerization is completed in the reactor, the polymerization is continued in the reactor to prepare meta-aramid fibrids, and the mechanical beating degree is 20SR;

[0065] After being made into paper with aramid short-cut fibers, the paper has a thickness of 0.05 mm, a tensile strength of 3000 N / m, a tear strength of 1000 mN, and an air permeability of 0.06 μm / (Pa·s).

[0066] Example 2

[0067] N-methylpyrrolidone was added to the reactor and cooled to 2°C. Metaphenylenediamine was added to dissolve into a 1.1 mol / L solution. The polymerization speed was 700 rpm. Isophthaloyl chloride was added twice with an interval of 15 minutes. The molar ratio of isophthaloyl chloride to metaphenylenediamine was 1.008:1. The first isophthaloyl chloride accounted for 30%. After the prepolymerization was completed, the polymer product entered the twin screw for polymerization. The twin screw speed was 600 rpm and the temperature was controlled at 45°C. After the polymerization reaction was completed, it was diluted and neutralized. The solid content of the diluted meta-aramid stock solution was 8% and the logarithmic viscosity was 1.3 dL / g. A coagulation bath was configured, with N-methylpyrrolidone accounting for 15% and the rest being water. The coagulation bath temperature was maintained at 30°C. The meta-aramid stock solution and the coagulation bath were injected into the high shear dispersion molding equipment at the same time, with a speed of 5000 rpm. The collected product is subjected to multiple water washing steps to obtain a meta-aramid fiber precipitation product, the mechanical beating degree of the product is 35SR, the fiber length is 0.6mm, and the fiber morphology is in the form of fiber strips or films under a microscope.

[0068] The above-mentioned meta-aramid fiber precipitation and aramid short-cut fibers are made into paper sheets in a papermaking machine at a ratio of 1:1. After high temperature and high pressure treatment, the paper sheets have a thickness of 0.05 mm, a tensile strength of 3800 N / m, a tear strength of 2300 mN, and an air permeability of 0.045 μm / (Pa·s).

[0069] Comparative Example 2

[0070] The difference from Example 1 is that after the prepolymerization is completed in the reactor, the polymerization is continued in the reactor to prepare meta-aramid fibrids, and the mechanical beating degree is 25SR;

[0071] After being made into paper with aramid short-cut fibers, the paper has a thickness of 0.05 mm, a tensile strength of 3300 N / m, a tear strength of 1300 mN, and an air permeability of 0.055 μm / (Pa·s).

[0072] Example 3

[0073] N-methylpyrrolidone was added to the reactor and cooled to 0°C. Metaphenylenediamine was added to dissolve into a 1.2 mol / L solution. The polymerization speed was 1000 rpm. Isophthaloyl chloride was added twice with an interval of 20 minutes. The molar ratio of isophthaloyl chloride to metaphenylenediamine was 1.005:1, and the first isophthaloyl chloride accounted for 50%. After the prepolymerization was completed, the polymer product entered the twin screw for polymerization. The twin screw speed was 700 rpm and the temperature was controlled at 50°C. After the polymerization reaction was completed, it was diluted and neutralized. The solid content of the diluted meta-aramid stock solution was 9% and the logarithmic viscosity was 1.6 dL / g. A coagulation bath was configured, with N-methylpyrrolidone accounting for 20% and the rest being water. The coagulation bath temperature was maintained at 20°C. The meta-aramid stock solution and the coagulation bath were injected into the high shear dispersion molding equipment at the same time, with a speed of 6000 rpm. The collected product is subjected to multiple water washing steps to obtain a meta-aramid fiber precipitation product, the mechanical beating degree of the product is 40SR, the fiber length is 0.7 mm, and the fiber morphology is in the form of fiber strips or films under a microscope.

[0074] The above-mentioned meta-aramid fibrils and aramid short fibers are made into paper sheets in a papermaking machine at a ratio of 1:1. After high temperature and high pressure treatment, the paper sheets have a thickness of 0.05 mm, a tensile strength of 4000 N / m, a tear strength of 2500 mN, and an air permeability of 0.04 μm / (Pa·s).

[0075] Comparative Example 3

[0076] The difference from Example 1 is that after the prepolymerization is completed in the reactor, the polymerization is continued in the reactor to prepare meta-aramid fibrids, and the mechanical beating degree is 20SR;

[0077] After being made into paper with aramid short-cut fibers, the paper has a thickness of 0.05 mm, a tensile strength of 3500 N / m, a tear strength of 1500 mN, and an air permeability of 0.05 μm / (Pa·s).

[0078] Example 4

[0079] N-methylpyrrolidone was added to the reactor and cooled to -2°C. Metaphenylenediamine was added to dissolve into a 1.3 mol / L solution. The polymerization speed was 1200 rpm. Isophthaloyl chloride was added twice with an interval of 25 minutes. The molar ratio of isophthaloyl chloride to metaphenylenediamine was 1.003:1. The first isophthaloyl chloride accounted for 70%. After the prepolymerization was completed, the polymer product entered the twin screw for polymerization. The twin screw speed was 800 rpm and the temperature was controlled at 55°C. After the polymerization reaction was completed, it was diluted and neutralized. The solid content of the diluted meta-aramid stock solution was 10% and the logarithmic viscosity was 1.9 dL / g. A coagulation bath was configured, with N-methylpyrrolidone accounting for 25% and the rest being water. The coagulation bath temperature was maintained at 10°C. The meta-aramid stock solution and the coagulation bath were injected into the high shear dispersion molding equipment at the same time, with a speed of 7000 rpm. The collected product is subjected to multiple water washing steps to obtain a meta-aramid fiber precipitation product, the mechanical beating degree of the product is 45SR, the fiber length is 0.8 mm, and the fiber morphology is in the form of fiber strips or films under a microscope.

[0080] The above-mentioned meta-aramid fibrils and aramid short fibers are made into paper sheets in a papermaking machine at a ratio of 1:1. After high temperature and high pressure treatment, the paper sheets have a thickness of 0.05 mm, a tensile strength of 4300 N / m, a tear strength of 2700 mN, and an air permeability of 0.035 μm / (Pa·s).

[0081] Comparative Example 4

[0082] The difference from Example 1 is that after the prepolymerization is completed in the reactor, the polymerization is continued in the reactor to prepare meta-aramid fibrids, and the mechanical beating degree is 20SR;

[0083] After being made into paper with aramid short-cut fibers, the paper has a thickness of 0.05 mm, a tensile strength of 3800 N / m, a tear strength of 1700 mN, and an air permeability of 0.045 μm / (Pa·s).

[0084] Example 5

[0085] N-methylpyrrolidone was added to the reactor and cooled to -5°C, and meta-phenylenediamine was added to dissolve into a 1.4 mol / L solution. The polymerization speed was 1500 rpm, and isophthaloyl chloride was added twice, with an interval of 30 minutes. The molar ratio of isophthaloyl chloride to meta-phenylenediamine was 1.0:1, and the first isophthaloyl chloride accounted for 90%. After the prepolymerization was completed, the polymer product entered the twin screw for polymerization. The twin screw speed was 900 rpm and the temperature was controlled at 60°C. After the polymerization reaction was completed, it was diluted and neutralized. The solid content of the diluted meta-aramid stock solution was 11%, and the logarithmic viscosity was 2.1 dL / g. A coagulation bath was configured, with N-methylpyrrolidone accounting for 30% and the rest being water, and the coagulation bath temperature was maintained at 0°C. The meta-aramid stock solution and the coagulation bath were injected into the high shear dispersion molding equipment at the same time, with a speed of 8000 rpm. The collected product is subjected to multiple water washing steps to obtain a meta-aramid fiber precipitate product, the mechanical beating degree of the product is 50SR, the fiber length is 0.9 mm, and the fiber morphology is in the form of fiber strips or films when observed under a microscope.

[0086] The above-mentioned meta-aramid fibrils and aramid short fibers are made into paper sheets in a papermaking machine at a ratio of 1:1. After high temperature and high pressure treatment, the paper sheets have a thickness of 0.05 mm, a tensile strength of 4500 N / m, a tear strength of 3000 mN, and an air permeability of 0.03 μm / (Pa·s).

[0087] Comparative Example 5

[0088] The difference from Example 1 is that after the prepolymerization is completed in the reactor, the polymerization is continued in the reactor to prepare meta-aramid fibrids, and the mechanical beating degree is 20SR;

[0089] After being made into paper with aramid short-cut fibers, the paper has a thickness of 0.05 mm, a tensile strength of 4000 N / m, a tear strength of 2000 mN, and an air permeability of 0.04 μm / (Pa·s).

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing meta-aramid fiber precipitates, comprising the following steps: a) prepolymerizing m-phenylenediamine and isophthaloyl chloride in a reaction kettle to obtain a prepolymer; b) polymerizing the prepolymer in a twin-screw reactor, and obtaining a meta-aramid fibrillation stock solution after dilution and neutralization; c) dispersing and molding the meta-aramid fibrid stock solution and the coagulation bath under the action of high shear, and washing the obtained product with water to obtain the meta-aramid fibrid.

2. The preparation method according to claim 1, characterized in that: The step a) comprises: The first part of isophthaloyl chloride is mixed with the m-phenylenediamine solution to perform a first prepolymerization; The second portion of isophthaloyl chloride is mixed with the first prepolymer to carry out a second prepolymerization to obtain a prepolymer.

3. The preparation method according to claim 2, characterized in that: The isophthaloyl chloride in the first part accounts for 10% to 90% of the total amount of the isophthaloyl chloride in the first part and the second part.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the total amount of isophthaloyl chloride in the first part and the second part to the m-phenylenediamine is 1.0-1.01:1; The temperature of the first prepolymerization and the second prepolymerization is independently -5°C to 5°C; The time of the first prepolymerization is 10 min to 30 min, and the time of the second prepolymerization is 20 min to 40 min.

5. The preparation method according to claim 1, characterized in that: In the step a), the prepolymerization solvent is N-methylpyrrolidone; The stirring speed of the prepolymerization is 500 rpm to 1500 rpm.

6. The preparation method according to claim 1, characterized in that: The rotation speed of the twin-screw reactor is 500 rpm to 1000 rpm; the polymerization temperature is 40° C. to 60° C.

7. The preparation method according to claim 6, characterized in that: The meta-aramid fiber precipitation stock solution has a solid content of 6% to 11% and a logarithmic viscosity of 1.0 dL / g to 2.1 dL / g.

8. The preparation method according to claim 1, characterized in that: In the step c), the coagulation bath is a mixture of N-methylpyrrolidone and water; The volume content of N-methylpyrrolidone in the coagulation bath is 5% to 30%; The temperature of the coagulation bath is 0°C to 40°C.

9. The preparation method according to claim 1, characterized in that: The high shear speed is 3000 rpm to 8000 rpm.

10. The meta-aramid fibrid prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Aramid fiber film as well as preparation method and application thereof

    CN120311397A

  • A method for preparing a modified meta-aramid fibrid

    CN122727974A